2008
DOI: 10.4067/s0718-27912008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Soil Aggregation

Abstract: Soil aggregation is governed by several biotic and abiotic components including landuse management. Aggregation is essential to maintain soil physical properties and facilitate biogeochemical cycling. Hyphae of arbuscular mycorrhizal fungi (AMF) are considered to be primary soil aggregators and there is a positively correlation between AMF hyphae and aggregate stability in natural systems. Recent evidence suggests that glomalin (GRSP), a glycoprotein produced by AMF hyphae which has a cementing capacity to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
2
26
0
3
Order By: Relevance
“…The bigger and more preserved microbial biomass in non-sterilized soil presents distinct functional characteristics and plays an essential role in soil aggregation (Six et al, 2004), as presented our results. Among soil microorganisms, AMF are the most important aggregation mediators, since they are the dominant component of the microbial biomass (Rillig, Steinberg, 2002;Borie, Rubio;Morales, 2008). We confirmed this affirmative in our study through outcomes presented and the positive and significant correlation between Cmic with MGD (r = 0.92, p<0.01) and MWD (r = 0.73, p<0.01).…”
Section: Treatmentssupporting
confidence: 85%
“…The bigger and more preserved microbial biomass in non-sterilized soil presents distinct functional characteristics and plays an essential role in soil aggregation (Six et al, 2004), as presented our results. Among soil microorganisms, AMF are the most important aggregation mediators, since they are the dominant component of the microbial biomass (Rillig, Steinberg, 2002;Borie, Rubio;Morales, 2008). We confirmed this affirmative in our study through outcomes presented and the positive and significant correlation between Cmic with MGD (r = 0.92, p<0.01) and MWD (r = 0.73, p<0.01).…”
Section: Treatmentssupporting
confidence: 85%
“…In spite of the fact that many articles have reported that the application of organic manures had negative impacts on AMF diversity (Sainz et al, 1998; Jacquot et al, 2000; Gryndler et al, 2008), several other studies have highlighted the positive influence of organic manure application on AMF population and diversity (Douds and Reider, 2003; Borie et al, 2008). Further, Albertsen et al (2006) reported that AMF in general seemed to thrive in soil amended with organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Spore density in undisturbed natural environment is higher than disturbed sites (Chanie and Assefa 2013;Muleta et al 2008). AMF plays a role in the formation of stable soil aggregates, building up a macroporous structure of soil that allows penetration of water and air and prevents erosion (Rillig 2004;Borie et al 2008;Aggarwal et al 2011); therefore, the application of AMF is of interest for the reclamation and revegetation of degraded lands (Miller and Jastrow 1992).…”
Section: Resultsmentioning
confidence: 99%